Settlement intention characteristics and determinants in floating populations in Chinese border cities. (May 2018) - You, Zhen; Yang, Hanbing; Fu, Meichen
Abstract: Floating populations are crucial for urbanization and economic development in China. Border cities are significant areas of population and economic agglomeration in border areas. The influx of floating populations into border cities has been an important impetus for urbanization of these border cities. Based on floating population dynamic monitoring data obtained from 22 border cities in 2014, we examined the characteristics of migrants and analyzed determinants of migrants' settlement intentions using chi-square tests and binary logistic regression analysis. The results revealed that human capital, economic conditions, family stability, social and living security, and social and cultural environment all influenced the settlement intentions of floating populations in border cities. Thus, local governments need to emphasize local socio-economic development and provide more social and living security to floating populations to encourage population inflow. Moreover, local governments need to promote and facilitate floating populations' integration into local communities.